Processing performance prediction method of battery positive electrode material and application thereof
By obtaining the physical and chemical properties parameters of the positive electrode material of lithium-ion battery, calculating processing values, predicting processing performance, and optimizing the additive formula through theoretical calculation models, the gels of the positive electrode material of lithium-ion battery in the process of slurry preparation and pole sheet processing are solved. The phenomenon, viscosity rebound and screening difficulties have achieved efficient and stable battery performance and reduction of production costs.
Patent Information
- Application Number
- CN202411494335.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art has problems such as gel phenomenon, viscosity rebound and screening difficulties in the process of slurry preparation and electrode sheet processing of lithium-ion battery positive electrode materials, resulting in unstable battery performance, and the dosage and proportion of additives need to be cumbersome. Experimental verification.
A method for predicting the processing performance of the positive electrode material of the battery is proposed. By obtaining the physical and chemical properties parameters of the positive electrode material (such as Dv50 particle size, specific surface area, residual alkali metal salt content), calculating the processing value with the calculation formula, predicting the processing performance of the material, and Optimize additive formulas through theoretical calculation models.
This method can accurately predict the processing performance of the positive electrode material, reduce the number of experiments, shorten the product development cycle, reduce production costs, improve battery performance stability, and realize intelligent control of automated production lines.
Smart Images

Figure BDA0005100874040000151 
Figure BDA0005100874040000162 
Figure BDA0005100874040000171
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to secondary batteries, and in particular to a method for predicting the processing performance of a positive electrode material for a battery and an application thereof. Background Art
[0002] With the continuous expansion of the new energy vehicle market, the demand for the installed capacity of secondary batteries has risen sharply. This trend has brought unprecedented challenges to the manufacturing process of secondary batteries. In particular, in the production chain of lithium-ion batteries, the slurry preparation and pole piece processing are particularly important and complex, because the performance of lithium-ion batteries is often directly related to the quality control of these key steps.
[0003] The two cathode materials widely used in lithium-ion secondary batteries are ternary cathode materials (LiNi x Co y Mn 1-x-y O2, 0<x, y<1, NCM) and lithium iron phosphate positive electrode material (LiFePO4, LFP). Among them, NCM positive electrode material has the advantage of high energy density, but in the process of slurry and pole piece processing, due to the residual alkali metal salt content on the surface of the material particles, the slurry will gel, and further production into lithium-ion batteries will affect the battery's electrical performance; LFP positive electrode material is more friendly to battery system safety, fast charging capacity and cycle life can meet consumer needs, but due to the small material particles and large specific surface area, gel agglomeration and viscosity rebound will affect the pole piece processing performance, and screening will be difficult after slurrying, and there will be problems such as particles, scratches, and foil leakage during the coating process.
[0004] In response to the above problems, the existing technology mainly improves the dispersibility and viscosity stability problems in the slurry preparation process by adding dispersants and other functional additives. For example, patent documents CN115340624A and CN115340624A disclose some dispersants for lithium-ion battery slurries. By adding dispersants, the dispersion of the slurry is significantly improved, the initial viscosity of the slurry is effectively reduced, and the viscosity rebound phenomenon is suppressed. At the same time, the gel phenomenon is prevented, thereby ensuring the smooth and efficient subsequent electrode processing. In addition, patent CN116722101A innovatively uses oxalic acid as an additive. By finely controlling the amount of oxalic acid added, it not only enhances the stability of the slurry, but also successfully solves the potential coagulation problem, further consolidating the stability of the electrode quality.
[0005] Although these patent documents have significantly improved the processing performance of slurry and electrode sheets through the use of additives, the dosage of additives and their optimal matching relationship with different raw materials still need to rely on tedious experimental verification and slurry performance testing, especially for the current situation of diversified raw material sources. Every time the raw materials are replaced or adjusted, additive ratio tests need to be carried out. This process is not only time-consuming and labor-intensive, but also increases production costs and resource consumption.
[0006] Based on this, if we can develop a method that can accurately predict the processability of positive electrode materials and their response to different amounts of additives, it will be possible to reduce the number of experiments in the early stages, thereby significantly shortening the product development cycle and saving production costs. Summary of the invention
[0007] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for predicting the processing performance of a positive electrode material for a battery, which can accurately predict the processability of the positive electrode material and its response to different amounts of additives.
[0008] The present invention also proposes the application of the above method.
[0009] According to one aspect of the present invention, a method for predicting the processing performance of a battery positive electrode material is proposed, comprising the following steps:
[0010] S1. Obtaining the physical and chemical property parameters of the positive electrode material, wherein the physical and chemical property parameters include the Dv50 particle size, specific surface area, and residual alkali metal salt content of the positive electrode material; calculating the processing value according to the physical and chemical property parameters of the positive electrode material and the amount of the positive electrode slurry dispersibility improvement agent added in combination with a calculation formula;
[0011] S2. Predicting the processing performance of the material according to the processing value: if the processing value is ≤ a threshold value, it is predicted that the positive electrode material has the processing performance that meets the expected requirements; if the processing value is > the threshold value, it is predicted that the positive electrode material does not have the processing performance that meets the expected requirements.
[0012] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved: The scheme of the present invention proposes an innovative prediction method, which is based on scientific and rigorous principles, and realizes accurate and reliable prediction of the processing performance of positive electrode materials by balancing the key intrinsic physical and chemical properties of positive electrode materials, including the interaction relationship between parameters such as particle size, residual alkali metal salt content and specific surface area. The prediction mechanism of the scheme of the present invention can screen out positive electrode materials with excellent processing performance in advance, effectively avoiding various challenges and problems that may arise in the subsequent electrode processing process (such as slurry, coating, and rolling processing sections), thereby significantly improving the overall performance stability of slurry and electrode sheets. Through the precise measurement and analysis of the intrinsic physical and chemical property parameters of positive electrode materials in the early stage, its processing performance can be predicted, which not only provides a scientific basis for material screening, but also greatly shortens the product development cycle. Furthermore, the present invention also incorporates a theoretical calculation model for quantitatively evaluating the potential impact of adding dispersibility-improving agents on material processing performance before and after, and optimizing the formula through theoretical calculation, without relying on the traditional, time-consuming and labor-intensive processing experiment trial and error process, it can directly guide the preparation of high-quality positive electrode sheets. The scheme of the present invention not only ensures that the electrochemical performance of the secondary battery remains excellent during long-term cyclic use and storage, but also achieves a significant reduction in production costs, including reducing the waste of human resources, shortening the research and development time, and effectively saving the use of raw materials. Therefore, the prediction method of the present invention not only represents a technological advancement in the field of materials science, but also provides strong technical support for the sustainable development of the secondary battery industry.
[0013] In some embodiments of the present invention, the calculation formula is as follows:
[0014] X=A*{ln[(bn)*c]-lgd}
[0015] Wherein, X is the processing value of the positive electrode material;
[0016] A is the dispersion coefficient. If the positive electrode material is not added with a positive electrode slurry dispersibility improving agent when preparing the slurry, A=1; if a positive electrode slurry dispersibility improving agent is added, A=1-100*a, where a is the percentage of the mass of the positive electrode slurry dispersibility improving agent to the total slurry, %;
[0017] b is the residual alkali metal salt content of the positive electrode material, ppm;
[0018] n is the empirical value of the standard residual alkali metal salt content, ppm;
[0019] c is the specific surface area of the positive electrode material, m 2 / g;
[0020] d is the Dv50 particle size of the positive electrode material, μm.
[0021] In some embodiments of the present invention, the battery is a lithium-ion battery. In some embodiments of the present invention, the positive electrode material of the lithium-ion battery includes at least one of a ternary positive electrode material, a lithium iron phosphate material, a lithium iron manganese phosphate material, a lithium cobalt oxide material, a lithium titanate material, and a lithium manganate material.
[0022] In some embodiments of the present invention, the value of a is 0≤a≤0.3%.
[0023] In some embodiments of the present invention, the value of n is 100≤n≤140 ppm.
[0024] In some embodiments of the present invention, the value of n is 120≤n≤130 ppm.
[0025] In some embodiments of the present invention, the threshold is ≤7.
[0026] In some embodiments of the present invention, the processing performance includes at least one of viscosity rebound, pole piece scratch cracking, and pole piece folded transmittance.
[0027] In some embodiments of the present invention, the expected processing performance includes the following performance when processed into a pole piece:
[0028] 1) At 25°C, viscosity rebound ≤ 10500mPa·s;
[0029] 2) The scratch and crack test result of the pole piece surface is qualified, wherein the judgment standard of the scratch and crack test result is: the pole piece surface is smooth and flat, or at least one of very few cracks, slight cracks, and slight scratches appears, then it is judged as qualified;
[0030] 3) The light transmittance of the folding crease is ≤10%.
[0031] In some embodiments of the present invention, the expected processing performance also includes that when processed into slurry, at least one of the slurry fineness or the discharge viscosity meets the expected conditions.
[0032] In some embodiments of the present invention, when the slurry is prepared, the expected condition of the slurry fineness is that the slurry fineness is ≤15 μm.
[0033] In some embodiments of the present invention, when the slurry is prepared, the expected condition of the slurry fineness is that the slurry fineness is ≤12 μm.
[0034] In some embodiments of the present invention, when formulated into a slurry, at 25° C., the expected condition of the discharge viscosity is that the discharge viscosity is ≤5000 mPa·s.
[0035] In some embodiments of the present invention, when formulated into a slurry, at 25° C., the expected condition of the discharge viscosity is that the discharge viscosity is ≤3000 mPa·s.
[0036] According to another aspect of the present invention, a method for preparing a positive electrode slurry for a battery is provided, comprising the following steps:
[0037] The positive electrode material having the expected processing performance is screened out by the above prediction method;
[0038] The positive electrode material, the conductive agent and the solvent I are added into the glue solution containing the binder and mixed to obtain the positive electrode slurry material.
[0039] According to another aspect of the present invention, a method for preparing a positive electrode sheet of a battery is provided, comprising the following steps:
[0040] The positive electrode slurry prepared by the above preparation method is coated on the current collector, dried, and roll-pressed to obtain the positive electrode slurry.
[0041] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved: through the prediction method of the scheme of the present invention, materials that do not meet the requirements can be screened out at the early stage of material preparation to avoid waste in the subsequent processing process. At the same time, the above prediction method can also be combined with an automated production line to better realize the intelligent control of the positive electrode sheet and battery production process and improve production efficiency; accurate prediction can reduce the trial and error cost in the production process, optimize the production process, and also reduce energy consumption and labor costs. Furthermore, by predicting the performance of new materials in the subsequent processing process, the screening and optimization process of new materials can be accelerated, thereby helping to promote the continuous progress and development of battery technology. Therefore, the prediction method of the scheme of the present invention has good application prospects in the fields of positive electrode slurry, positive electrode sheet and lithium battery manufacturing.
[0042] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is an example diagram of a situation determined as a severe scratch in a specific embodiment of the present invention;
[0044] Figure 2 This is an example diagram of a situation determined as having very few cracks in a specific embodiment of the present invention;
[0045] Figure 3 is an example diagram of a situation determined as a slight crack in a specific embodiment of the present invention;
[0046] Figure 4This is an example diagram of a situation determined as a slight crack in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0047] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.
[0048] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0049] In the description of the present invention, "greater than", "less than", "exceed" and the like are understood to exclude the number itself. If I and II are described, they are used to distinguish technical features, and cannot be understood to indicate or imply relative importance or implicitly indicate the number of the indicated technical features or implicitly indicate the order of the indicated technical features.
[0050] The industrial standard value of residual lithium content is defined as 130ppm based on current industrial level and experience, which is obtained through batch verification.
[0051] The dispersant may be any commercially available dispersant in the art.
[0052] In the description of the present invention, the temperature during the viscosity rebound and discharge viscosity tests is both 25°C.
[0053] In some embodiments of the present invention, a method for predicting the processing performance of a positive electrode material of a battery is provided, comprising the following steps:
[0054] S1. Obtaining the physical and chemical property parameters of the positive electrode material, wherein the physical and chemical property parameters include the Dv50 particle size, specific surface area, and residual alkali metal salt content of the positive electrode material; calculating the processing value according to the physical and chemical property parameters of the positive electrode material and the amount of the positive electrode slurry dispersibility improvement agent added in combination with a calculation formula;
[0055] S2. Predicting the processing performance of the material according to the processing value: if the processing value is ≤ a threshold value, it is predicted that the positive electrode material has the processing performance that meets the expected requirements; if the processing value is > the threshold value, it is predicted that the positive electrode material does not have the processing performance that meets the expected requirements.
[0056] The prediction mechanism of the scheme of the present invention can screen out positive electrode materials with excellent processing performance in advance, effectively avoiding various challenges and problems that may arise in the subsequent electrode processing process (such as slurry, coating, and rolling processing), thereby significantly improving the overall performance stability of the slurry and the electrode. Through the precise measurement and analysis of the intrinsic physical and chemical properties of the positive electrode material in the early stage, its processing performance can be predicted, which not only provides a scientific basis for material screening, but also greatly shortens the product development cycle.
[0057] In some embodiments of the present invention, the calculation formula is as follows: X=A*{ln[(bn)*c]-lgd};
[0058] Wherein, X is the processing value of the positive electrode material;
[0059] A is the dispersion coefficient. If the positive electrode material is not added with a positive electrode slurry dispersibility improving agent when preparing the slurry, A=1; if a positive electrode slurry dispersibility improving agent is added, A=1-100*a, where a is the percentage of the mass of the positive electrode slurry dispersibility improving agent to the total slurry, %;
[0060] b is the residual alkali metal salt content of the positive electrode material, ppm;
[0061] n is the empirical value of the standard residual alkali metal salt content, ppm;
[0062] c is the specific surface area of the positive electrode material, m 2 / g;
[0063] d is the Dv50 particle size of the positive electrode material, μm.
[0064] The theoretical calculation model of the scheme of the present invention is used to quantitatively evaluate the potential impact on the material processing performance before and after the addition of the dispersibility-improving reagent. The formula is optimized through theoretical calculation, without relying on the traditional, time-consuming and labor-intensive processing experiment trial and error process, and can directly guide the preparation of high-quality positive electrode sheets without processing defects.
[0065] When calculating X, ignore the dimensions of b, n, c, and d, and simply substitute the values of the corresponding dimensional levels to obtain the result.
[0066] In some embodiments of the present invention, the battery is a lithium-ion battery.
[0067] In some embodiments of the present invention, the residual alkali metal salt content is the residual lithium salt content.
[0068] In some embodiments of the present invention, the physical and chemical property parameters of the positive electrode material can be obtained directly from the purchaser, or can be obtained through testing.
[0069] In some embodiments of the present invention, the value of a is 0≤a≤0.3%. When the value of a is non-zero, the value of A will change accordingly, such as when 0.1% by mass of the positive electrode slurry dispersibility improving agent is added, A is 0.9; when 0.2% by mass of the dispersibility improving agent is added, A is 0.8.
[0070] In some embodiments of the present invention, the residual alkali metal salt content of the positive electrode material is obtained by a potentiometric drop test, or can be obtained by other instrument tests.
[0071] In some embodiments of the present invention, the residual alkali metal salt content industrial standard value is a residual alkali metal salt content industrial standard value formulated according to the current industrial level, and may change with the degree of advancement of the technology for removing the residual alkali metal salt content during the preparation of the positive electrode material.
[0072] In some embodiments of the present invention, the value of n is 100≤n≤140 ppm.
[0073] In some embodiments of the present invention, the value of n is 110≤n≤135 ppm.
[0074] In some embodiments of the present invention, the value of n is 120≤n≤130 ppm.
[0075] In some embodiments of the present invention, the value of n is 125≤n≤130 ppm.
[0076] In some embodiments of the present invention, the value of n is 130 ppm. According to current industrial level and experience, it is preferably 130 ppm.
[0077] In some embodiments of the present invention, the specific surface area of the positive electrode material is measured by a nitrogen adsorption specific surface area tester, or can be measured by other instruments.
[0078] In some embodiments of the present invention, the Dv50 particle size of the positive electrode material is obtained by testing with a Malvern particle size analyzer, or may be obtained by testing with other instruments.
[0079] In some embodiments of the present invention, the positive electrode slurry dispersibility improving agent can be a dispersant or other auxiliary additives for improving slurry dispersibility. Common dispersants for lithium-ion battery positive electrode slurries include PVP dispersants and new dispersants such as polyethers and polyesters.
[0080] In some embodiments of the present invention, the threshold value is ≤ 7. A suitable threshold value range can significantly improve the accuracy of the prediction method and more accurately predict the processing performance of the positive electrode material.
[0081] In some embodiments of the present invention, the threshold is equal to 7. When the threshold is set to 7, the standard can efficiently screen out positive electrode materials with relatively good performance. Although under this standard, some selected materials (mainly materials with processing values close to the threshold) may show slight defects in subsequent processing, these defects are usually within a controllable range and are not sufficient to significantly affect the overall processing requirements, so they can still meet the basic requirements of the processing process. The setting of this threshold is based on a careful consideration of the balance between material properties and processing adaptability, aiming to ensure processing efficiency while maximizing the comprehensive utilization of materials.
[0082] However, if the application scenario places more stringent requirements on the processing performance of the positive electrode material, or aims to pursue higher product quality, this can be achieved by further adjusting the threshold standard. Specifically, the threshold can be set to a lower value than 7, such as 6.97 or lower. This reduction in the threshold means that the screening conditions are tightened, which will exclude more materials that are slightly insufficient in subtle performance, thereby ensuring that the screened positive electrode materials show higher stability and consistency during processing. Of course, this tightened screening standard may also lead to a decrease in the pass rate of material screening. It is necessary to weigh the pros and cons in actual operations and make reasonable choices based on specific needs.
[0083] Therefore, by flexibly adjusting the threshold standard, the performance of the positive electrode material can be effectively controlled and optimized while ensuring that the processing requirements are met.
[0084] In some embodiments of the present invention, the processing performance includes at least one of viscosity rebound, pole piece scratch cracking, and pole piece folded transmittance.
[0085] In some embodiments of the present invention, the expected processing performance includes the following performance when processed into a pole piece:
[0086] 1) At 25°C, viscosity rebound ≤ 10500mPa·s;
[0087] 2) The scratch and crack test result of the pole piece surface is qualified, wherein the judgment standard of the scratch and crack test result is: the pole piece surface is smooth and flat, or at least one of very few cracks, slight cracks, and slight scratches appears, then it is judged as qualified;
[0088] 3) The light transmittance of the folding crease is ≤10%.
[0089] If severe cracks or scratches occur, it will be judged as unqualified.
[0090] In some embodiments of the present invention, the scratches or cracks of the pole piece are detected and determined by appearance inspection. The severity can be determined based on the experience of inspectors in this field, such as severe cracks refer to more than 2 cracks per square centimeter of the pole piece; severe scratches refer to more than 2 scratches in a 40cm*40cm inspection area.
[0091] In some embodiments of the present invention, the scratch determination standard levels are: none, slight, and severe, wherein none means no scratch, slight means one scratch, and severe means two or more scratches.
[0092] In some embodiments of the present invention, the cracking degree is judged by the following levels: none, few cracks, slight cracks and severe cracks. The crack size is judged by referring to IEC 60086-1-2015, and the crack size requirement is 0.05 mm. Among them, none means no cracks, and few cracks means no more than 1 crack per square centimeter (e.g. Figure 2 The left side of the figure is judged as no cracks, and the right side can be judged as very few cracks. In the figure, the diameter of the disc is 25mm). Slight cracks refer to no more than 2 cracks per square centimeter (for example Figure 3 The left side of the figure is judged as no cracks, and the right side can be judged as slight cracks. In the figure, the diameter of the disc is 25 mm). Severe cracks refer to more than 2 cracks per square centimeter (for example Figure 4 The left side of the picture is judged as no cracks, while the right side can be judged as severe cracks. In the picture, the diameter of the disc is 25mm).
[0093] In some embodiments of the present invention, a surface is defined as smooth and flat if it is free of cracks and scratches.
[0094] In some embodiments of the present invention, the expected processing performance also includes that when processed into slurry, at least one of the slurry fineness or the discharge viscosity meets the expected conditions.
[0095] In some embodiments of the present invention, when formulated into a slurry, the expected condition for the fineness of the slurry is that the slurry fineness ≤ 15 μm. If the slurry fineness is too large, it may cause the slurry to easily settle, resulting in a poor consistency of the slurry, which in turn affects the coating process, leading to phenomena such as material blockage, scratches on the electrode sheet, and uneven coating during the coating process. In addition, during the roll pressing process, a slurry with too large a fineness is also likely to cause microcracks or fractures in the electrode sheet. Therefore, controlling the slurry fineness within a certain range can better ensure the performance of the electrode sheet.
[0096] In some embodiments of the present invention, when formulated into a slurry, the expected condition for the fineness of the slurry is that the slurry fineness ≤ 12 μm.
[0097] In some embodiments of the present invention, when formulated into a slurry, at 25 °C, the expected condition for the discharge viscosity is that the discharge viscosity ≤ 5000 mPa·s. The slurry viscosity may vary among different enterprises and processes and can be adjusted and optimized as needed to achieve the best coating effect and battery performance.
[0098] In some embodiments of the present invention, when formulated into a slurry, at 25 °C, the expected condition for the discharge viscosity is that the discharge viscosity ≤ 3000 mPa·s.
[0099] In some embodiments of the present invention, the positive electrode material of the lithium-ion battery includes at least one of a ternary positive electrode material, a lithium iron phosphate material, a lithium manganese iron phosphate material, a lithium cobalt oxide material, a lithium titanate material, and a lithium manganese oxide material. The prediction method of the present invention is applicable to various positive electrode materials for secondary batteries, including but not limited to the above positive electrode materials, and can also be other positive electrode materials suitable for more secondary batteries.
[0100] In some embodiments of the present invention, the ternary positive electrode material includes at least one of a nickel cobalt manganese ternary material and a nickel cobalt aluminum ternary material.
[0101] In some embodiments of the present invention, the nickel cobalt manganese ternary material includes at least one of a medium-nickel positive electrode material and a high-nickel positive electrode material.
[0102] In some embodiments of the present invention, the chemical formula of the medium-nickel positive electrode material is LiNi x1 Co y1 Mn 1-x1-y1 O2, 0.5 ≤ x1 < 0.8, 0 ≤ y1 ≤ 0.5, 0 < x1 + y1 ≤ 1. For example, x1 can be 0.5, 0.6, 0.7, 0.75, etc.; y1 can be 0.02, 0.06, 0.15, 0.2, 0.4, etc.
[0103] In some embodiments of the present invention, the chemical formula of the high-nickel positive electrode material is LiNi x2 Coy2 Mn 1-x2-y2 O2, where 0.8 ≤ x2 ≤ 1.0, 0 ≤ y2 ≤ 0.2, and 0 < x2 + y2 ≤ 1. For example, x2 can be 0.8, 0.9, 0.93, 0.95, etc.; y2 can be 0.02, 0.06, 0.1, 0.15, etc.
[0104] In some embodiments of the present invention, the surface of the lithium iron phosphate particles in the lithium iron phosphate material contains a carbon coating layer.
[0105] In some embodiments of the present invention, the chemical formula of the lithium iron phosphate is LiFePO4.
[0106] In some embodiments of the present invention, the mass fraction of the carbon coating layer is 0.1 - 3%. The carbon coating layer accounts for 0.1 - 3% of the total mass of the lithium iron phosphate material. For example, it can be 0.1%, 0.3%, 0.8%, 1.2%, 2.0%, 2.5%, 3.0%, etc.
[0107] In some embodiments of the present invention, the chemical formula of the lithium manganese iron phosphate in the lithium manganese iron phosphate material is LiMn x3 Fe 1-x3 PO4, where 0.2 ≤ x3 ≤ 0.8. For example, x3 can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc.
[0108] In some embodiments of the present invention, the surface of the lithium manganese iron phosphate particles in the lithium manganese iron phosphate material contains a carbon coating layer, and the mass fraction of the carbon coating layer is 0.1 - 3%. For example, it can be 0.1%, 0.3%, 0.8%, 1.2%, 2.0%, 2.5%, 3.0%, etc.
[0109] According to another aspect of the present invention, a method for preparing a battery cathode slurry is provided, which includes the following steps:
[0110] Select a cathode material with processing performance meeting the expectations through the above prediction method;
[0111] Add the cathode material, a conductive agent, and solvent I into a binder-containing glue solution and mix them to obtain the cathode slurry material.
[0112] In some embodiments of the present invention, the method for preparing the binder-containing glue solution includes the following steps: Dissolve the binder in solvent II.
[0113] In some embodiments of the present invention, solvent I and solvent II are the same or different.
[0114] In some embodiments of the present invention, the solvent I and the solvent II are independently selected from at least one of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), and dimethylformamide (DMF).
[0115] In some embodiments of the present invention, both the solvent I and the solvent II are NMP.
[0116] In some embodiments of the present invention, the binder may be a conventional binder.
[0117] In some embodiments of the present invention, the binder is a fluorine-based polymer and / or a synthetic rubber, and is further preferably one or a combination of at least two of polyvinyl fluoride, polyvinylidene fluoride (PVDF), polytetrafluoroethylene, styrene-butadiene rubber, fluorine-based rubber or ethylene propylene diene rubber.
[0118] In some embodiments of the present invention, typical but non-limiting examples of the combination include: a combination of polyvinyl fluoride and polyvinylidene fluoride, a combination of polytetrafluoroethylene and styrene-butadiene rubber-type rubber, a combination of styrene-butadiene rubber-type rubber, fluorine-based rubber and ethylene propylene diene rubber, a combination of polytetrafluoroethylene, styrene-butadiene rubber-type rubber and fluorine-based rubber, a combination of polyvinyl fluoride, polyvinylidene fluoride, polytetrafluoroethylene and styrene-butadiene rubber-type rubber, a combination of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber-type rubber, fluorine-based rubber and ethylene propylene diene rubber, etc., with polyvinylidene fluoride being particularly preferred.
[0119] In some embodiments of the present invention, the conductive agent can be a conventional conductive agent, such as conductive carbon black (such as acetylene black, Super P, Super S, 350G or Ketjen black), conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15 or Ks-6), carbon fiber or carbon nanotubes.
[0120] Conductive agents are used to ensure that the electrodes have good charge and discharge performance. A certain amount of conductive material is usually added during the production of the electrode sheet. It collects microcurrents between active materials and between active materials and current collectors to reduce the contact resistance of the electrodes and accelerate the movement rate of electrons. It can also effectively increase the migration rate of lithium ions in the electrode materials, thereby improving the charge and discharge efficiency of the electrodes. Conventional conductive agents in the field can be selected and added in conventional amounts without any restrictive provisions.
[0121] In some embodiments of the present invention, the raw materials for preparing the positive electrode slurry include positive electrode materials, conductive agents and binders in a mass ratio of (89-96): (1-4): (1-7). The positive electrode slurry of the battery contains a certain proportion of conductive agents and binders, which is conducive to the positive electrode material being better attached to the current collector when making the pole piece, thereby improving the charge and discharge efficiency of the positive electrode. It can be 89:1:3, 90:2:4, 92:3:5, 94:1.5:3.5, 94:1:3, 94:2:4, 95:1:3, 95:2:5, 95:3:2 or 96:2:5, including but not limited to the listed values. At the same time, other values not listed in the numerical range are also applicable.
[0122] According to another aspect of the present invention, a method for preparing a positive electrode sheet of a battery is provided, comprising the following steps:
[0123] The positive electrode slurry prepared by the above preparation method is coated on the current collector, dried, and roll-pressed to obtain the positive electrode slurry.
[0124] In some embodiments of the present invention, the current collector may be at least one of pure aluminum foil, carbon-coated aluminum foil or composite pure foil. The current collector, as an indispensable support and conductive medium for the mixed active positive electrode material, plays a vital role in the electrochemical energy storage device. It not only stably carries the mixed active positive electrode material to ensure its structural stability during the charging and discharging process, but also conducts electrons efficiently through its excellent conductive properties, thereby establishing a smooth current path between the positive and negative electrodes. This function plays a significant role in improving the overall performance of the battery, enhancing the energy conversion efficiency and extending the cycle life.
[0125] Specifically, the current collector is usually made of highly conductive materials, such as various aluminum foils, which can effectively reduce the internal resistance of the battery and reduce the loss of energy during transmission. At the same time, the design of the current collector must also consider good contact with the active material to ensure that the current can be evenly distributed to avoid performance degradation or safety hazards caused by local overheating or excessive current density.
[0126] In some embodiments of the present invention, when the positive electrode slurry is coated on the current collector, the surface density is 100 to 400 g / m 2 For example, it can be 100g / m 2 , 200g / m 2 , 300g / m 2 , 400g / m 2By limiting the electrode surface density within the above range, it is possible to ensure the selection of a suitable compaction density of the electrode, and avoid problems such as poor ion conductivity caused by incomplete electrolyte infiltration. Too low electrode surface density affects the energy density of the positive electrode; too high electrode surface density will lead to polarization and deteriorate the electrochemical performance of the battery cell.
[0127] In some embodiments of the present invention, the drying adopts a drying process, which can be a conventional drying process to save production costs.
[0128] In some embodiments of the present invention, the drying temperature of the electrode is 80-130°C. Conventional drying parameters can be selected without special optimization. For example, it can be 90°C, 110°C, or 130°C. By limiting the drying temperature to the above range, the evaporation rate of the solvent can be controlled, and at the same time, it can be better ensured that there are no cracks on the surface of the material, and cracks caused by improper processing can be avoided. In addition, it can also promote the curing of the binder, so that the positive electrode has excellent mechanical strength and stability.
[0129] In some embodiments of the present invention, the drying time is 5-20 minutes. For example, it can be 5 minutes, 10 minutes, 15 minutes, etc. By limiting the drying time to the above range, the curing of the positive electrode sheet can be promoted to ensure the stability and consistency of the positive electrode sheet.
[0130] In some embodiments of the present invention, the rolling pressure is 50-120T. For example, it can be 70T, 80T, 90T, 110T, etc. By limiting the rolling pressure within the above range, it can be ensured that the positive electrode sheet reaches the ultimate compaction density, while ensuring that the sheet has excellent mechanical strength and consistency.
[0131] Example 1
[0132] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a medium nickel positive electrode material with a chemical formula of LiNi 0.68 Co 0.10 Mn 0.22 O2 (hereinafter referred to as "Medium Nickel 1"). The specific prediction steps are as follows:
[0133] S1. Measure the physical and chemical property parameters of the positive electrode material, including the Dv50 particle size, specific surface area, and residual alkali metal salt content (residual lithium) content of the positive electrode material (specific parameter values are shown in Table 1 below); calculate the processing value based on the physical and chemical property parameters of the positive electrode material and the dispersant addition information combined with the calculation formula.
[0134] The particle size of the material is obtained by testing with a Malvern particle size analyzer, the specific surface area is obtained by testing with a nitrogen adsorption specific surface area tester, and the residual alkali metal salt content (residual lithium) is obtained by testing with a potentiometric titrator.
[0135] S2. Predicting the processing performance of the material according to the processing value: if the processing value is <7, it is predicted that the positive electrode material has the expected processing performance, otherwise it is predicted that the positive electrode material does not have the expected processing performance;
[0136] The calculation formula is as follows: X = A*{ln[(bn)*c]-lgd};
[0137] Where X is the processing value of the positive electrode material;
[0138] A is the dispersion coefficient. When the positive electrode material is prepared into slurry, no dispersant is added, so A=1;
[0139] b is the residual lithium content of the positive electrode material, ppm;
[0140] n is the industrial standard value of residual lithium content, ppm; the industrial standard value of residual lithium is formulated according to the current industrial level, and in this embodiment, n=130;
[0141] c is the specific surface area of the positive electrode material, m 2 / g;
[0142] d is the Dv50 particle size of the positive electrode material, μm.
[0143] The expected processing performance includes the following conditions:
[0144] 1) When prepared into slurry, the viscosity of the material at 25°C is not more than 5000mPa·s;
[0145] 2) When prepared into slurry, the slurry fineness is not greater than 15 μm;
[0146] 3) When processed into pole pieces, the viscosity rebound is ≤10500mPa·s at 25°C;
[0147] 4) When processing into pole pieces, no serious cracks or scratches appear;
[0148] 5) When processed into pole pieces, the transmittance of the folding mark is ≤10%.
[0149] Example 2
[0150] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a medium nickel positive electrode material with a chemical formula of LiNi 0.68 Co 0.10 Mn 0.22O2 (hereinafter referred to as "Medium Nickel 2") is different from Example 1 in that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0151] Example 3
[0152] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a medium nickel positive electrode material with a chemical formula of LiNi 0.68 Co 0.10 Mn 0.22 O2 (hereinafter referred to as "Medium Nickel 3") is different from Example 1 in that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0153] Example 4
[0154] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a medium nickel positive electrode material with a chemical formula of LiNi 0.68 Co 0.10 Mn 0.22 O2 (hereinafter referred to as "Medium Nickel 4") is different from Example 1 in that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0155] Example 5
[0156] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiNi 0.91 Co 0.07 Mn 0.02 O2 (hereinafter referred to as "high nickel 1") is different from Example 1 in that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0157] Example 6
[0158] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiNi 0.91 Co 0.07 Mn 0.02 O2 (hereinafter referred to as "high nickel 2") is different from Example 1 in that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0159] Example 7
[0160] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiNi 0.90 Co 0.07 Mn 0.03O2 (hereinafter referred to as "high nickel 3") is different from Example 1 in that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0161] Example 8
[0162] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiNi 0.90 Co 0.07 Mn 0.03 O2 (hereinafter referred to as "high nickel 4") is different from Example 1 in that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0163] Example 9
[0164] This example provides a method for predicting the processing performance of a positive electrode material for a lithium-ion battery. The positive electrode material for a lithium-ion battery is specifically a high-nickel positive electrode material with a chemical formula of LiFePO4 (hereinafter referred to as "lithium iron 1"). The difference between this example and Example 1 is that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0165] Example 10
[0166] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiFePO4 (hereinafter referred to as "lithium iron 2"). The difference between this example and Example 1 is that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0167] Embodiment 11
[0168] This example provides a method for predicting the processing performance of a positive electrode material for a lithium-ion battery. The positive electrode material for a lithium-ion battery is specifically a high-nickel positive electrode material with a chemical formula of LiFePO4 (hereinafter referred to as "lithium iron 3"). The difference between this example and Example 1 is that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0169] Example 12
[0170] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiNi 0.91 Co 0.07 Mn 0.02 O2 (hereinafter referred to as "high nickel 2+ dispersant"). The difference between this embodiment and embodiment 6 is that a dispersant is added when preparing the slurry, the amount of the dispersant added is 0.2%, and the value of A is 0.8.
[0171] Embodiment 13
[0172] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiMn 0.6 Fe 0.4 PO4 (hereinafter referred to as "manganese iron lithium 1 + dispersant"). The difference between it and Example 1 is that the physical and chemical property parameter values of the material are different, see Table 1 for details. When preparing the slurry, a dispersant is added, the amount of the dispersant added is 0.2%, and the value of A is 0.8.
[0173] Embodiment 14
[0174] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiMn 0.6 Fe 0.4 PO4 (hereinafter referred to as "manganese iron lithium 2+ dispersant"). The difference between it and Example 1 is that the physical and chemical property parameter values of the material are different, see Table 1 for details. When preparing the slurry, a dispersant is added, the amount of the dispersant added is 0.2%, and the value of A is 0.8.
[0175] Comparative Example 1
[0176] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiMn 0.6 Fe 0.4 PO4 (hereinafter referred to as "manganese iron lithium 1") is different from Example 13 in that no dispersant is added and A=1.
[0177] Comparative Example 2
[0178] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiMn 0.6 Fe 0.4 PO4 (hereinafter referred to as "manganese iron lithium 2") is different from Example 14 in that no dispersant is added and A=1.
[0179] Comparative Example 3
[0180] This example provides a method for predicting the processing performance of a lithium-ion battery positive electrode material. The lithium-ion battery positive electrode material is specifically a high-nickel positive electrode material with a chemical formula of LiMn 0.6 Fe 0.4 PO4 (hereinafter referred to as "manganese iron lithium 3") is different from Example 1 in that the physical and chemical property parameter values of the material are different, see Table 1 for details.
[0181] The physical and chemical property parameters of each material obtained in the above embodiments and comparative examples are shown in Table 1 below. At the same time, for the convenience of viewing, the processing value results calculated according to the processing value calculation formula are also summarized in Table 1.
[0182] Table 1
[0183]
[0184]
[0185] Therefore, according to the calculation results in Table 1, it can be seen that each material in each solution of the embodiment of the present invention will have the expected processing performance and basically no processing risk.
[0186] In order to verify the accuracy of the above prediction method, the materials in the above embodiments are processed into positive electrode slurry and positive electrode sheets by conventional methods.
[0187] The raw materials for preparing the slurry are composed of a positive electrode material, a conductive agent, a binder and a solvent, wherein the positive electrode material is the positive electrode material in the above embodiment or comparative example, the conductive agent is a mixture of conductive carbon black and carbon nanotubes, the binder is polyvinylidene fluoride, and the solvent is NMP. The specific process of preparing the slurry is as follows:
[0188] A positive electrode material, a conductive agent and a solvent are added to a glue solution containing a binder, wherein the solvent in the glue solution and the solvent used in preparing the slurry are both NMP, the mass ratio of the positive electrode material, conductive carbon black, carbon nanotubes and polyvinylidene fluoride is 95:2:1:2, and the solid content in the slurry is 72%.
[0189] Furthermore, the slurry is processed into positive electrode sheets. The specific process is as follows:
[0190] Apply the slurry (single side 150g / m 2 ) on both sides of the current collector, dried (110°C, 10min), and then roller pressed to obtain the positive electrode sheet.
[0191] The slurry viscosity and discharge viscosity of the slurry were tested. At the same time, the viscosity rebound of the electrode, the scratches and cracks on the surface of the electrode, and the transmittance of the folding crease were also tested. The results are shown in Table 2 below.
[0192] Table 2
[0193]
[0194]
[0195] Note: Scratch judgment standard level: none, slight, severe, among which, none means no scratch, slight means one scratch, and severe means two or more scratches (for example Figure 1The situation shown can be judged as severe scratches. The size of the pole piece in the figure is 40cm*40cm);
[0196] The cracking degree is determined by the following levels: none, very few cracks, slight cracks and severe cracks. The crack size determination standard refers to "IEC 60086-1-2015", and the crack size requirement is 0.05mm. Among them, none means no cracks, and very few cracks means no more than 1 crack per square centimeter (for example Figure 2 The left side of the figure is judged as no cracks, and the right side can be judged as very few cracks. In the figure, the diameter of the disc is 25mm). Slight cracks refer to no more than 2 cracks per square centimeter (for example Figure 3 The left side of the figure is judged as no cracks, and the right side can be judged as slight cracks. In the figure, the diameter of the disc is 25 mm). Severe cracks refer to more than 2 cracks per square centimeter (for example Figure 4 The left side of the picture is judged as no cracks, while the right side can be judged as severe cracks. In the picture, the diameter of the disc is 25mm).
[0197] If the test results of scratches and cracks are both negative, the statistical results are normal, and the others are recorded according to abnormal items.
[0198] As can be seen from Table 2 above, the prediction method of the scheme of the present invention is accurate and reliable. As can be seen from the above table, the medium nickel material with the structural characteristics of the scheme of the present invention has no processing problems during the slurry, coating and rolling processes, and the processing value of the small-particle high-nickel material is close to 7, and there are slight processing defects, which can be solved by adding a dispersant, and it can be seen from Example 13 that the problem is effectively solved by adding a dispersant. Large-particle high-nickel positive electrode materials have good processing performance and no processing risks. The processing value of lithium iron phosphate materials with high residual alkali metal salt content is close to 7, and there are also slight processing defects, but the overall performance of the pole piece is less affected. The manganese iron lithium material with a smaller particle size also has a higher residual alkali metal salt content. Therefore, its processing value is at a higher level, and the verification results also show that it has more serious processing problems. Adding a dispersant can improve processing problems, and the experimental results also show that the addition of a dispersant effectively improves its processing performance and better solves the various problems that exist when it is processed into a pole piece.
[0199] Furthermore, the positive electrode sheet and the negative electrode sheet are stacked, injected, and packaged to prepare a battery cell. The prepared battery cell has excellent electrochemical performance.
[0200] In summary, the prediction method of the scheme of the present invention can accurately and reliably predict whether the processing performance of the positive electrode material meets expectations; at the same time, when encountering risks and challenges that may be encountered during the processing of some materials, the calculation model in the prediction method of the present invention can predict whether this risk challenge can be solved by adding reagents that improve dispersibility, which not only effectively avoids the high cost and time consumption caused by a large number of trial and error experiments required in traditional methods, but also realizes the active prevention and control of processing risks and substantial savings in economic costs. Therefore, the prediction scheme of the present invention not only significantly improves production efficiency, but also greatly reduces material waste, energy consumption and time costs, opening up a new path for the intelligent and refined development of the manufacturing industry.
[0201] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for predicting the processing performance of a battery positive electrode material, characterized in that: The steps include: S1. Obtaining the physical and chemical property parameters of the positive electrode material, wherein the physical and chemical property parameters include the Dv50 particle size, specific surface area, and residual alkali metal salt content of the positive electrode material; calculating the processing value according to the physical and chemical property parameters of the positive electrode material and the amount of the positive electrode slurry dispersibility improvement agent added in combination with a calculation formula; S2. Predicting the processing performance of the material according to the processing value: if the processing value is ≤ a threshold value, it is predicted that the positive electrode material has the processing performance that meets the expected requirements; if the processing value is > the threshold value, it is predicted that the positive electrode material does not have the processing performance that meets the expected requirements.
2. The method for predicting processing performance of a positive electrode material for a battery according to claim 1, characterized in that: The calculation formula is as follows: X = A*{ln[(bn)*c]-lg d}; Wherein, X is the processing value of the positive electrode material; A is the dispersion coefficient, A = 1-100*a, a is the mass percentage of the positive electrode slurry dispersion improvement agent to the total slurry, %; b is the residual alkali metal salt content of the positive electrode material, ppm; n is the empirical value of the standard residual alkali metal salt content, ppm; c is the specific surface area of the positive electrode material, m 2 / g; d is the Dv50 particle size of the positive electrode material, μm.
3. The method for predicting processing performance of a positive electrode material for a battery according to claim 1, characterized in that: The battery is a lithium-ion battery.
4. The method for predicting processing performance of a positive electrode material for a battery according to claim 3, characterized in that: The positive electrode material of the lithium-ion battery includes at least one of a ternary positive electrode material, a lithium iron phosphate material, a lithium iron manganese phosphate material, a lithium cobalt oxide material, a lithium titanate material, and a lithium manganate oxide material.
5. The method for predicting processing performance of a positive electrode material for a battery according to any one of claims 2 to 4, characterized in that: The value of a is 0≤a≤0.3%; and / or, the threshold value is ≤7; and / or, the value of n is 100≤n≤140ppm; preferably, the value of n is 120≤n≤130ppm.
6. The method for predicting processing performance of a positive electrode material for a battery according to any one of claims 1 to 4, characterized in that: The processing performance includes at least one of viscosity rebound, scratch cracking of the pole piece, and transmittance of the pole piece when folded; preferably, the processing performance that meets expectations includes the following performance when processed into a pole piece: 1) At 25°C, viscosity rebound ≤ 10500mPa·s; 2) The scratch and crack test result of the pole piece surface is qualified, wherein the judgment standard of the scratch and crack test result is: the pole piece surface is smooth and flat, or at least one of very few cracks, slight cracks, and slight scratches appears, then it is judged as qualified; 3) The light transmittance of the folding crease is ≤10%.
7. The method for predicting processing performance of a positive electrode material for a battery according to claim 6, characterized in that: The expected processing performance also includes at least one of the following properties when processed into slurry: a) Slurry fineness ≤ 15 μm; b) At 25°C, the discharge viscosity is ≤5000mPa·s.
8. A method for preparing a positive electrode slurry for a battery, characterized in that: The steps include: Screening out a positive electrode material having expected processing performance by the prediction method according to any one of claims 1 to 7; The positive electrode material, the conductive agent and the solvent I are added into the glue solution containing the binder and mixed to obtain the positive electrode slurry material.
9. A method for preparing a positive electrode sheet of a battery, characterized in that: The steps include: The positive electrode slurry prepared by the preparation method as claimed in claim 8 is coated on the current collector, dried, and roll-pressed to obtain the product.
10. The method for preparing a positive electrode sheet of a battery according to claim 9, characterized in that: The preparation method satisfies at least one of the following conditions during the preparation process: 1) When the positive electrode slurry is coated on the current collector, the surface density is 100 to 400 g / m 2 ; 2) The drying process is a drying process, the drying temperature of the electrode is 80-130° C.; and / or the drying time is 5-20 min; 3) The rolling pressure is 50-120T.
Citation Information
Patent Citations
Polymer, conductive paste, positive electrode sheet, secondary battery, and electric device
CN115340624A
Cited By
Two-dimensional particle size evaluation method and evaluation system for particle dispersibility and cracking degree
CN121113806A
Rapid pre-evaluation method for processing performance of electrode active material
CN121741123A